Food supplements based on palmitoylethanolamide plus hydroxytyrosol from olive tree or Bacopa monnieri extracts for neurological diseases - Kiani, Aysha Karim; Miggiano, Giacinto Abele Donato; Aquilanti, Barbara; Velluti, Valeria; Matera, Giuseppina; Gagliardi, Lucilla; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Neurological disorders like Parkinson disease and Alzheimer disease, spinal cord injury and stroke have some recurrent characteristics such as abnormal protein aggregation, oxidative stress induction, apoptosis, excitotoxicity, perturbation of intracellular Ca2+ homeostasis and inflammation. To date, there are few effective treatments available and the drugs currently used to manage the symptoms have important side effects. Therefore, research studies are focusing on natural phytochemicals present in diet as bioactive molecules potentially useful against neurodegenerative diseases. In this review, we will discuss the neuroprotective role of palmitoylethanolamide, hydroxytyrosol, and Bacopa monnieri extracts against neuroinflammation and neurodegeneration, thereby revealing their remarkable potential as novel therapeutic options for the treatment of neurodegenerative disorders.